2015
DOI: 10.3390/rs70607615
|View full text |Cite
|
Sign up to set email alerts
|

A Collection of SAR Methodologies for Monitoring Wetlands

Abstract: Abstract:Wetlands are an important natural resource that requires monitoring. A key step in environmental monitoring is to map the locations and characteristics of the resource to better enable assessment of change over time. Synthetic Aperture Radar (SAR) systems are helpful in this way for wetland resources because their data can be used to map and monitor changes in surface water extent, saturated soils, flooded vegetation, and changes in wetland vegetation cover. We review a few techniques to demonstrate S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
137
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(143 citation statements)
references
References 88 publications
1
137
0
2
Order By: Relevance
“…Due to the high spatial and temporal variations of flooded areas, validation of flood maps over relatively wide areas derived from SAR imagery remains challenging. Higher accuracies are observed in other studies with validations based either on limited visual ground observations [31] or by comparison with multispectral satellite observations [15]. Both methods have limitations in terms of spatial coverage and temporal monitoring.…”
Section: Grassland Floods (Intra-field Scale)mentioning
confidence: 74%
“…Due to the high spatial and temporal variations of flooded areas, validation of flood maps over relatively wide areas derived from SAR imagery remains challenging. Higher accuracies are observed in other studies with validations based either on limited visual ground observations [31] or by comparison with multispectral satellite observations [15]. Both methods have limitations in terms of spatial coverage and temporal monitoring.…”
Section: Grassland Floods (Intra-field Scale)mentioning
confidence: 74%
“…We found that within each subdivision of the lake, the differences between image pairs (LST and radar) appeared to be random, with no systematic pattern within or across the subdivisions as a function of time. There is a substantial publication record (e.g., [22][23][24][25])) for the use of radar data for mapping wetlands including flooded vegetation. Wilusz et al (2017) [22] found that "low resolution C-band SAR imagery shows promise for long term study of Sudd wetland flood dynamics."…”
Section: Resultsmentioning
confidence: 99%
“…Radar has the advantage over LST of a relatively extensive history of use for mapping flooded vegetation. According to [24], "SAR (Synthetic Aperture Radar) has many characteristics that make it ideal for mapping and monitoring water and wetlands over time." According to [26], "What is evident throughout the recent literature is that multidimensional radar data sets are attaining an accepted role in operational situations needing information on wetland presence, extent and conditions."…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, they also provide cultural services to their visitors, such as aesthetic, recreation and a wilderness feeling. These are some of the reasons why many wetlands have become protected areas [1]. Wetlands face…”
Section: Introductionmentioning
confidence: 99%